TEACHER STRATEGIES FOR INSTILLING AN ATTITUDE OF TOLERANCE IN STUDENTS IN RESPONDING TO DIFFERENCES IN BELIEFS - Arifin, Syamsul; Khoiroh, Ummul; Aini, Tsamar Nur; Putri, Dinda Febrianti; Sahidah, Ahmad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Instilling an attitude of tolerance in students is a strategic step in creating a learning environment that is inclusive, harmonious and supports diversity. This article discusses the importance of tolerance as an effort to build harmony amidst the diversity of society, avoid conflict, and strengthen unity. Using library research methods, this article identifies strategies that teachers can implement, such as integrating diversity in the curriculum, implementing cross-cultural activities, and developing class discussions. The role of teachers as role models, mediators and facilitators is very important in encouraging students to understand diversity as richness. Apart from that, collaboration with parents and the community can strengthen the value of tolerance outside of school. This article concludes that education based on tolerance can create a generation that is ready to live side by side peacefully amidst plurality.